Institutional Work for Corruption in Indonesian Public Budgeting and Procurement - Rijadh Djatu Winardi (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
This paper examines how institutionalized corruption in public institutions is planned and executed within Indonesia's formal budgeting process. It explores how key corrupt actors secure procurement projects well before the actual budgeting process takes place. Additionally, this paper seeks to highlight how a network of corruption, involving significant actors from parliament, government, and corporations, is organized. Drawing on data from court examination records, court judgments, and newspapers, we synthesize the experiences of corrupt actors and witnesses within the corrupt network. Conceptually informed by the institutional work perspective, this article analyzes a major scandal in Indonesia's budgeting and procurement, the e-ID procurement scandal, and supported by several smaller cases. We illustrate how corrupt practices are embedded in budgeting procedures and find that bribery and gift-giving play a crucial role in the creation and planning of corrupt activities. The implications of our findings for anti-corruption initiatives are also discussed.